Protein Content in Snake Fruit Cultivar Pondoh (Salacca edulis Reinw.) with Aseptic Condition in Room Storage - Yulian Dwi Anggraeni Puspa Handoko; Ahmad Ni'matullah Al-Baarri; Anang Mohamad Legowo; Mulyana Hadipernata; Wisnu Broto (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2019)
Snake fruit is a type of tropical fruit with high market demand, however it is easily damaged and approximately ± 7 days at room temperature of shelf life. After 3 days of harvest, quality of snake fruit has decrease in chemical components, such as color, hardness, and proximate. The decline in the quality may also be caused by microbial contamination. This study aimed to determine the protein content of snake fruit during storage at room temperature under aseptic condition. This study was done in storage temperature of 25±5ºC and carried out at 3 times repetition. The protein content of snake fruit was observed for 3 days. The results showed that protein content of snake fruit at the beginning of storage were about 0.5%. Then, the protein content decreased until undetectable by the Kjeldahl method on the third day of storage. As conclusion, the three days of decrease in the protein content could be determined.